Membangun Kesiapsiagaan Masyarakat Terhadap Bencana Banjir Melalui Edukasi Tas Siaga Bencana Di Dusun Curah Lele Kabupaten Jember: - Mohammad Ali Hamid; Desta Almiira Hudoyo; Ananda Maqfirotul Hasanah; Meritania Nurittama; Vinda Anayu Aprilia; Ratna Annisa Nur Aulia; Fikhih Wahyu Islamy; Pandu Wibowo (Jurnal Pakar Pengabdian Kesehatan, 2026)
Flood is one of the most frequent hydrometeorological disasters in Jember Regency and may affect community health, safety, and daily activities. Curah Lele Hamlet, Wonoasri Village, is a flood-prone area that requires improved community preparedness. This study aimed to describe community preparedness toward flood disasters through disaster preparedness bag education. A one-group pretest-posttest design was used involving 14 residents of Curah Lele Hamlet. The intervention was delivered through lectures and discussions supported by leaflets. Preparedness was measured using questionnaires before and after the educational program. The results showed that all respondents (100%) were categorized as having good preparedness in both pretest and posttest assessments. Disaster preparedness bag education helped maintain and strengthen community understanding of disaster preparedness, particularly regarding the functions and contents of a preparedness bag. This activity can serve as a family- and community-based disaster mitigation strategy in flood-prone areas.